A RARE CASE OF CONGENITAL ANORCHIA PRESENTED AS GYNAECOMASTIA IN ADULTHOOD - Woon, Yip Xiong; Chua, Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Congenital anorchia is a rare condition characterised by the absence of testes in a 46,XY individual with a male phenotype. The incidence appears to be 1:20,000 males. The lack of testosterone production will lead to issues with puberty, bone health and fertility. CASE A 28-year-old male with no known medical illness presented to us at the age of 21 with absence of secondary sexual characteristics and gynaecomastia since entering pubertal period. A thorough physical examination revealed a male with a height of 171 cm with a BMI of 28.7 kg/m2 with Tanner 1 pubic hair, and absence of axillary hair and moustache. His male sexual organs were prepubertal and his scrotum was empty. His parents noticed the empty scrotum since his neonatal period but did not seek further medical attention. An MRI was done revealing a micropenis without visualised testes in the abdomen or pelvis. Further hormonal panels showed primary hypogonadism with a very low testosterone level of 0.62 nmol/L (Normal range: 8.6-29). Thyroid function and prolactin were normal. Chromosomal analysis revealed a 46, XY karyotype. He was then started with intramuscular testosterone injection at 22-years-old. CONCLUSION The most common cause of congenital primary hypogonadism is sex chromosome aneuploidy, present in Turner syndrome and Klinefelter syndrome. Studies have shown that about 4.5 percent out of 6000 cryptorchid children are anorchid, and 14 percent of them have absence of bilateral testes. A hypothesis of vascular occlusion in early foetal development leading to atrophy of functional testes was made. It is supported by findings of a fibrotic node at the end of vasa differentia in anorchid patients. Congenital anorchia is rarely seen among the male population. It is congenital and presents late to clinical setting if missed during childbirth. Testosterone replacement is essential for secondary sexual characteristics and bone health.